Análise da relação entre o retorno anormal e o volume anormal de negociações das ações que compõem o índice Bovespa - Oliveira, Alexandre Silva de (2008)
The theme of research of the proposed dissertation is the analysis of the relationship among the abnormal return and the abnormal volume of negotiations of the actions that it composes the index Ibovespa. As subjects are investigated which the dynamic and contemporary relationship between the abnormal return and abnormal volume and enter the volatility of the abnormal return and the abnormal volume, and which the dynamic and contemporary relationship between the return of the action and negotiated volume and enter the volatility of the return and the negotiated volume. As research method grew bibliographical researches and I study of the temporary series of the actions that composed the index Ibovespa on May 30, 2008, treated with the use of regressions multiple behind, with the model GJR-GARCH and with the analysis of causality of Granger. As results the work doesn't allow conclusive statements with relationship the significância of the relationships sees that in some actions the relationship exists in a significant way and in other no, however it shows that the volume can be used as prognostic of the movement of the prices for some actions in matter in traders operations in the use of technical analysis.